2020
DOI: 10.1101/2020.11.02.365825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Hsc70 Disaggregation Machinery Removes Monomer Units Directly from α-Synuclein Fibril Ends

Abstract: Molecular chaperones contribute to the maintenance of cellular protein homeostasis through a wide range of mechanisms, including the assistance of de novo protein folding, the rescue of misfolded proteins, and the prevention of amyloid formation. Chaperones of the Hsp70 family have a striking capability of disaggregating otherwise irreversible aggregate structures such as amyloid fibrils that accumulate during the development of neurodegenerative diseases. However, the mechanisms of this key emerging functiona… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Hsp/c70s have two known mechanisms of mitigating protein misfolding: an ATPcycling dependent "foldase" action, which is able to restore damaged proteins, and an ATP-independent "holdase" mode, which binds to unfolded proteins to prevent aggregation (23). Although in concert with cochaperones Hsp70 can disaggregate ASyn fibrils in an ATP-cycling mode (24,25), Hsp/c70s block ASyn fibrillization (26)(27)(28)(29)(30)(31)(32)(33) in an ATP-independent manner (27)(28)(29)(30)(31)(32), indicating a "holdase"-based mechanism. It has been assumed that this holdase-like activity was mediated via Hsp/ c70's canonical substrate-binding site in the SBD, which is required for other known holdase roles (34).…”
mentioning
confidence: 99%
“…Hsp/c70s have two known mechanisms of mitigating protein misfolding: an ATPcycling dependent "foldase" action, which is able to restore damaged proteins, and an ATP-independent "holdase" mode, which binds to unfolded proteins to prevent aggregation (23). Although in concert with cochaperones Hsp70 can disaggregate ASyn fibrils in an ATP-cycling mode (24,25), Hsp/c70s block ASyn fibrillization (26)(27)(28)(29)(30)(31)(32)(33) in an ATP-independent manner (27)(28)(29)(30)(31)(32), indicating a "holdase"-based mechanism. It has been assumed that this holdase-like activity was mediated via Hsp/ c70's canonical substrate-binding site in the SBD, which is required for other known holdase roles (34).…”
mentioning
confidence: 99%
“…Surprisingly, we found that Skp 3 and SurA act synergistically on uOmpX aggregates, suggesting higher order interactions between both periplasmic chaperones. Disaggregation mechanisms have also been observed in the ATP-dependent cytoplasmic chaperones of Hsp70 family 68,69 . However, both Skp and SurA disaggregate oligomeric structures in the absence of an external energy source, thereby supporting the known disaggregase DegP, with a yet to be determined mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…We therefore speculated that surface effects may lead to electrostatic interactions. We therefore employed a microfluidics-based technology (Arosio et al, 2016;Scheidt et al, 2019;Schneider et al, 2020) to characterize the receptor ligand interaction via diffusional sizing.…”
Section: Promiscuous Binding Of α-Synuclein Fibrils Questions Selectivity Towards Lag3mentioning
confidence: 99%
“…The samples were incubated at room temperature for 60 minutes and the size of the formed immunocomplex was determined through measuring the hydrodynamic radius, Rh, with microfluidic diffusional sizing, as described above. Dissociation constants (KD) were determined using the Langmuir binding isotherm, as previously reported (Schneider et al, 2020),…”
Section: Microfluidics Diffusional Sizingmentioning
confidence: 99%